Long-Term Effectiveness and Cost-Effectiveness of Metformin Combined with Liraglutide or Exenatide for Type 2 Diabetes Mellitus Based on the CORE Diabetes Model Study. - Xuesong Zhang; Sisi Liu; Yukun Li; Yan Wang; Meimei Tian; Guoqiang Liu (PLoS ONE, 2016)
BACKGROUND:Type 2 diabetes mellitus (T2DM) is associated with β cell impairment. Agonists of the glucagon-like peptide 1 (GLP-1) receptor (such as liraglutide and exenatide) can increase the number of pancreatic β cells and improve cell function. These drugs contribute to the long-term control of T2DM. OBJECTIVE:To evaluate the cost-effectiveness of metformin combined with liraglutide or exenatide in Chinese patient with T2DM. METHODS:Patients with T2DM from the Third Hospital of Hebei Medical University were treated with oral metformin combined with liraglutide (0.6 mg/day, could be increased by 0.6 mg weekly until 1.2 or 1.8 mg) or exenatide (5 μg bid for four weeks, increased to 10 μg bid). The computer simulation model CORE was used to calculate the 30-year expected life expectancy, quality-adjusted life years (QALY), direct costs, HbA1c levels, body mass index (BMI), and the incidence of cardiovascular, renal, and ocular complications of T2DM. Patients were followed up for 52 weeks. Medication costs were calculated according to retail prices in China. A 3% annual discount was adopted in this study. RESULTS:The 30-year simulation showed that the total direct medical costs were lower using liraglutide compared to exenatide by 2130 RMB/QALY yearly, while the expected life expectancy and QALY were increased by 0.471 years and 0.388, respectively, using liraglutide with an incremental cost-effectiveness of -11,550 RMB/QALYs. CONCLUSION:Liraglutide 1.2 mg/day was superior to exenatide 10 μg bid with respect to cost-effectiveness in Chinese patients with T2DM.